Turnover intention among academics: A case study of private higher learning education in Klang Valley - Ramli A.A.; Salahudin S.N.; Zainol Z.; Suandi T. (Universiti Putra Malaysia, 2023)
Academics are seen as guardians of knowledge, disseminators of knowledge and creators of new knowledge. However, due to the expectation of Malaysia to be a regional hub for international higher education, it consequently burdens the academics especially in private higher learning education. Stress occurs among academics and stimulates them to leave. This situation is dangerous as it impacts on the institution and the student itself directly and indirectly. Therefore, this study attempts to investigate turnover intention from the perspective of job demand, job control and social support. 201 academics from private HLE were participated in this research and the empirical tests revealed that job control determine the level of turnover intention as well as social support on turnover intention. The regression estimation shows that social support was significantly refected in turnover intention among academics. © Universiti Putra Malaysia Press.